The location of activities of manufacturing multinationals in the Asia-Pacific - Enright, Michael J (Journal of International Business Studies, 2009)
Analysis of survey results from 440 manufacturing multinationals active in the Asia-Pacific shows that there are significant differences in the patterns of location decisions for different corporate activities in the region. Analysis of a random effects mixed model of activity location suggests relationships between a variety of location and firm attributes and foreign investment in different activities, and shows that the patterns of significance among the explanatory variables differ across different activities. The results are consistent with the view that firm activities, along with resources and knowledge, should be viewed as fundamental components of the multinational firm.